2016
DOI: 10.3390/su8040325
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Building Apartments for University Talent through the Agent Construction Mode in China: Interrelationship and Prioritization

Abstract: Apartments for university talent (AUT), are apartments provided to staff at non-market price, in order to attract outstanding scholars from around the world to work in universities and improve educational quality. This has been a critical issue in achieving social sustainability in China during rapid urbanization and industrialization. The agent construction mode has been adopted to build AUT because universities usually lack relevant management experience. The agent construction mode is a type of turnkey engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It uses the basics of graph theory and employs interactive learning to exploit theoretical, conceptual, and computational leverage to illustrate a contextual relationship among variables. Thus, ISM identifies inter-relationships among variables to build a concrete model [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…It uses the basics of graph theory and employs interactive learning to exploit theoretical, conceptual, and computational leverage to illustrate a contextual relationship among variables. Thus, ISM identifies inter-relationships among variables to build a concrete model [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Jha and Devaya [35] modeled the risks faced by Indian construction companies assessing international projects. Liu et al [36] identified risk factors of building apartments for University talent through the agent construction mode in China. In this vein, Hachicha and Elmsalmi [37] proposed an integrated approach based-structural modeling for risk prioritization in the supply network management.…”
Section: The Supply Chain Risk Managementmentioning
confidence: 99%
“…Nevertheless, the Chinese construction industry is a major construction market globally. Furthermore, the Chinese construction market is different from other construction industries in many respects, including the participants' poor education and their uneven level of quality, as well as the imperfection of the laws and regulations [32][33][34][35]. Thus, it is both important and necessary to extract the behavioral risks among principal participants in Chinese construction.…”
Section: Behavioral Risk In the Construction Industrymentioning
confidence: 99%